Spectrally efficient TWR‐aided free‐space optical communication over turbulent channel with generalized pointing error. Issue 4 (16th June 2016) - Sharma, Nikhil; Bansal, Ankur; Garg, Parul
Abstract: In this paper, the performance of two‐way relay assisted optical wireless communication is analysed. The optical wireless communication system performance is corrupted by atmospheric‐induced turbulence and the generalized pointing errors. A three node, dual hop, bi‐directional system employing decode‐and‐forward relaying phenomena are considered. The conventional one‐way relay assisted system is spectrally inefficient because of the half duplex losses incurred, whereas the proposed two‐way relay assisted system achieves spectral efficiency by managing bi‐directional communication in two time slots, thus maximizing the achievable rate of the network. The closed‐form expressions of probability density function for composite Gamma–Gamma turbulence impaired by generalized pointing errors are derived. Furthermore, we provide the closed‐form expression of cumulative distribution function of the equivalent end‐to‐end signal‐to‐noise ratio. In capitalizing on these derived statistics, we conduct outage and error rate analysis of the considered system. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, the performance of two‐way relay‐assisted optical wireless communication is analyzed. The optical wireless communication system performance is corrupted by atmospheric‐induced turbulence and the generalized pointing errors. A three‐node, dual‐hop, bi‐directional system employing decode‐and‐forward relaying phenomena is considered.